Seasonal dynamics of indicators of metabolism and oxygen transport system of blood of athletes-skiers of Khanty-Mansiysk - Stepanov, A. S.; Gubina, A. E.; Koinosov, An. P.; Pogonyshev, D. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate seasonal changes in the parameters of metabolism, blood oxygen transport system and physical performance of athletes specializing in cross-country skiing and biathlon in the conditions of Khanty-Mansiysk.